Renal function and cardiovascular outcomes after living donor nephrectomy in the UK: quality and safety revisited. (25th June 2013) - Patel, Nilay; Mason, Phil; Rushton, Sally; Hudson, Alex; Ploeg, Rutger; Friend, Peter; Sinha, Sanjay; Sullivan, Mark
<x xml:space="preserve">Abstract</x> Objective To determine renal function and cardiovascular outcomes after living donor nephrectomy (LDN). Living donor kidney transplantation has become established as the treatment of choice for end‐stage renal failure. Benefits to the recipient have to be balanced against perioperative and long‐term health risks to the donor. Subjects/Patients and Methods The UK Transplant Registry (UKTR) was used to identify 4586 living donors who had donated a kidney for transplantation in the UK between 2001 and 2008. This study was conducted with the consent and support of the NHS Blood and Transplant (NHSBT) Kidney and Pancreas Research Group. Results The mean glomerular filtration rate (GFR) fell from 103 mL/min/1.73 m2 before LDN to 58 mL/min/1.73 m2 1 year after LDN. At 1 year after LDN 60% of donors had a GFR of <60 mL/min/1.73 m2. A GFR of <60 mL/min/1.73 m2 after LDN was associated with older age, females, lower GFR before LDN, White ethnicity, earlier LDN period, unrelated donor type and body mass index of >25 kg/m2. Over a 2‐year period after LDN there was an overall mortality rate of 0.39%, cardiovascular death in one patient (mortality rate of 0.02%) and a major cardiovascular event rate of 0.44%. Conclusion In this study we show that mild renal dysfunction is common after LDN; however, due to the short duration of follow‐up we are unable to comment on whether this subsequently leads to an increased risk of developing of cardiovascular disease.